Shadowing Pathologies of Diaphragm Wall Concretes: General Overview (Global Journals of Research in Engineering, 2024)
This paper provides a general overview regarding shadowing pathologies that have been observed on diaphragm walls after excavation This phenomenon also termed mattressing by the European Federation of Foundation Contractors and the Deep Foundation Institute on wall panels as its name suggests is the imprint of the reinforcement cage in the concrete block While some mattressing is not necessarily evaluated as defect durability issues put at risk the integrity of the structure In some cases the steel reinforcing bars are directly exposed to the open air promoting corrosion phenomena and thus harming the entire structure Upon investigating the preliminary findings of the scientific literature this article has defined the factors that are likely to affect the occurrence of these anomalies These factors may be divided into three main families diaphragm wall components executed techniques during construction and interactions between the components throughout the different construction stages Recommendations presented by previous studies are also discussed
Keywords: diaphragm wall; shadowing pathology; mattressing; deep foundations